2016
DOI: 10.1186/s40900-016-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating public involvement in research design and grant development: Using a qualitative document analysis method to analyse an award scheme for researchers

Abstract: Plain English summaryThe National Institute for Health Research (NIHR) Research Design Service (RDS) for Yorkshire and Humber has been running a public involvement funding scheme since 2008. This scheme awards researchers a small amount of money to help them get involvement from patients and/or the public. Involvement activities take place at the time when researchers are planning studies, and when they are completing application forms to request funding for a proposed research project. After the public involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 11 publications
1
58
0
Order By: Relevance
“…The critical review identified 10 publications for inclusion, shown in Table 1 [ 30 33 , 48 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The critical review identified 10 publications for inclusion, shown in Table 1 [ 30 33 , 48 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…One publication was a methodology chapter [ 31 ], and the others were empirical studies using qualitative methodologies: thematic analysis [ 30 , 33 , 49 , 52 ], qualitative content analysis [ 33 , 48 ], interpretative phenomenological analysis [ 51 ], grounded theory [ 32 ] and framework analysis [ 48 , 50 , 53 ]. There was strong consensus across all studies that including co-researchers with lived experience in qualitative research data analysis produced richer, more in-depth and alternative understandings of the material that the academic researchers could not have developed on their own.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations